The Representation of Violence and Injustice in Saw (2004) Movie: A Forensic Linguistics Perspective - Az Zahra Rizani; Moh. Iqbal Firdaus; Eka Ugi Sutikno (Universitas Islam Negeri Palopo, 2026)
Following Stuart Hall's theory of representation, this research uses forensic linguistics to examine how violence and injustice are represented in the Saw (2004) movie. The research aims to uncover how language is used to construct ideological meanings surrounding violence and injustice in the film. Using a qualitative descriptive method and content analysis, the research focuses on the dialogues, monologues, and narrative elements in Saw (2004) that reflect acts of physical and verbal violence, discrimination, and violations of human rights. The findings reveal that language is employed not merely to drive the plot, but to shape psychological manipulation, moral dilemmas, and systems of control. Jigsaw’s use of commands, threats, and rhetorical devices portrays violence as moral retribution, while injustice is masked through coercive choices and oppressive structures. Forensic linguistic markers such as modality, imperative forms, metaphor, and evaluative language play a central role in constructing these representations. This research contributes to forensic linguistics and English education by demonstrating how language in popular media can encode power relations and ideological messages, highlighting the need for critical media literacy in academic settings.